2011
DOI: 10.2147/ppa.s11251
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid dermal fillers: can adjunctive lidocaine improve patient satisfaction without decreasing efficacy or duration?

Abstract: Hyaluronic acid (HA) dermal fillers are the most widely used injectables to augment facial volume without surgery. HA dermal fillers are popular because of their ease of administration, predictable effectiveness, good safety profile, and quick patient recovery. The most common patient complaint is pain. Our goal is to review the current literature on HA fillers and compare outcomes with and without lidocaine. We found adjunctive lidocaine significantly decreases pain during injection and postinjection with cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…In addition, previous studies have shown that the addition of lidocaine to collagen-based dermal fillers resulted in less swelling and bruising [17], potentially due to the antihistaminergic effect of lidocaine on mast cells [18]. Similar findings have been reported for hyaluronic acid-based dermal fillers mixed with lidocaine, also showing a reduction in swelling, erythema, and bruising [16, 1921]. As lidocaine is suggested to decrease these side effects, this is also expected for the PCL-based dermal filler mixed with lidocaine.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, previous studies have shown that the addition of lidocaine to collagen-based dermal fillers resulted in less swelling and bruising [17], potentially due to the antihistaminergic effect of lidocaine on mast cells [18]. Similar findings have been reported for hyaluronic acid-based dermal fillers mixed with lidocaine, also showing a reduction in swelling, erythema, and bruising [16, 1921]. As lidocaine is suggested to decrease these side effects, this is also expected for the PCL-based dermal filler mixed with lidocaine.…”
Section: Discussionsupporting
confidence: 68%
“…Physicians have reported no decrease in clinical efficacy after mixing the PCL dermal filler with lidocaine with or without epinephrine, as has also been reported for hyaluronic acid-based dermal fillers containing lidocaine (for review, see Smith and Cockerham [21]). Planned (pre)clinical studies with lidocaine premixed before treatment and lidocaine incorporated in the PCL dermal filler syringe itself are aimed at confirming this.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have shown that lidocaine integrated into the filler reduced the perception of pain during the injection and correlated with higher patient satisfaction. 26 Although injection site reactions such as redness, swelling, and bruising are expected with any type of dermal filler injection, 17 only 1 event of redness was reported. Consistently, most patients in the present study stated their willingness to repeat the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronic acid has a long history of cosmetic use; in 1989, Balasz and Denlinger described the first HA developed as a dermal filler,1,36 and HA dermal fillers have been used for soft tissue augmentation since the 1990s 1. The first BDDE-crosslinked HA filler was made available in Europe in 1996, and since then the safety profile of this type of product has been extensively studied.…”
Section: Clinical Safety Of Ha Fillersmentioning
confidence: 99%
“…The technology and biocompatibility of the products has progressed along with this demand, from the use of silicone injections in the 1940s and 1950s and the first animal-derived collagen fillers of the 1980s through to the introduction of hyaluronic acid (HA) fillers in the 1990s 1. HA fillers, according to a survey of plastic surgeons conducted by the International Society of Aesthetic Plastic Surgeons (ISAPS), were the second-most-popular nonsurgical procedure of 2010, with more than two million procedures performed 2.…”
mentioning
confidence: 99%